Postexercise immune-inflammatory improvement in type 2 diabetes is associated with baseline insulin resistance - Cheng, Wei; Guo, Kai; Zhang, Xuelian; Zhang, Keqin (Frontiers in Endocrinology, 2025)
PurposeTo examine how baseline insulin resistance (IR) modulates exercise-induced changes in systemic immune-inflammation index (SII) and metabolic parameters in type 2 diabetes mellitus (T2DM).MethodsFifty-five T2DM patients stratified by fasting C-peptide tertiles into low- (Group 1), moderate- (Group 2), and high-IR groups (Group 3) completed a 4-week moderate-intensity combined aerobic-resistance exercise program. Changes in SII (neutrophils × platelets/lymphocytes), anthropometrics, and glucolipid markers were assessed, with ANCOVA and hierarchical regression modeling intergroup differences and predictors (Clinical Trial Registration ID: ChiCTR2200066710).ResultsSignificant reductions in weight, BMI, and body fat% occurred in Group 1/Group 2 (all p<0.05) but not Group 3. SII decreased in Group 1 (p<0.05) yet increased in Group 3 due to neutrophil elevation (p<0.05). Fasting glucose and HbA1c improved across all groups (p<0.05), with Group 3’s glycemic benefits independent of weight loss or anti-inflammatory effects. Baseline C-peptide independently predicted increases in ΔSII across all adjusted models (β=19.85–21.94, p<0.01), whereas covariates including age, diabetes duration, and BMI showed no significant effects.ConclusionSevere baseline IR attenuates exercise-mediated SII improvement and body composition optimization, whereas glycemic benefits remain IR-independent, necessitating IR-stratified exercise prescriptions.Clinical trial registrationChinese Clinical Trial Registry, identifier ChiCTR2200066710.